Impact of Ghutka and Mawa Use on Oral Health in a Sub-Urban Population of Karachi: Impact of Ghutka and Mawa on Oral Health in Karachi - Khatri, Vijay Kumar; Munir, Hafsa; Gauhar, Tooba Mahmud; Iqbal, Khalid; Kumari, Devi; Kumar, Roop (Pakistan Journal of Health Sciences, 2025)
Ghutka and Mawa are smokeless tobacco products mostly used in South Asia. They have areca nut, tobacco, lime, catechu, paraffin wax, and flavoring materials. These mixtures are highly addictive and cancer-causing, related to oral submucous fibrosis, leukoplakia, and mouth cancers. Still, awareness of their harmful effects remains very low among users. Objectives: To observe oral findings and clinical patterns in Ghutka and Mawa users visiting ENT clinics. Methods: This cross-sectional research was done in Al-Tibri Medical College and Hospital, Karachi, from January to June 2025. One hundred patients who used Ghutka or Mawa for at least six months were selected by purposive sampling. Oral history and a detailed mouth examination were done. Data was entered and analyzed in SPSS using the Chi-square test, with a significance level p ≤ 0.05. Results: Out of 100 users, dental issues were most common (73%), then trismus (44%), pain (40%), and chewing trouble (21%). The majority were addicted for 6–20 years, while 11 had more than 20 years of use. Ulcers were found in 58 Mawa and 53 Ghutka users; growths in 35 and 29 respectively. Longer use had more severe lesions, with malignant signs mostly after 10 years (p < 0.05). Conclusions: Ghutka and Mawa are strongly connected with ulcers, dental and jaw problems, and precancerous growths. Long-term use increases damage. Awareness, early detection, and strict public control are urgently required.